Determinants of species diversity, abundance and habitat associations of the anuran fauna from forest fragments in Cavite, Luzon Island, Philippines - Causaren, Rubie Maranan (Animo Repository, 2012)
Anuran diversity, richness, abundance, and habitat associations were studied in 6 secondary lowland forest fragments in Cavite. Eighty-two (82) standardized 100 x 10 m strip transects were sampled from February to September 2010 employing a combination of strip transect sampling, time-constrained searches, visual encounter survey (VES), and acoustic encounter survey (AES). Detailed habitat recordings were also taken at each strip transect and PCQM was used to determine tree composition. A total of 17 anuran species, including 5 species representing new records for Cavite, was recorded. Two species, Platymantis sp. and Kaloula sp., are also believed to be possible Cavite endemics. Fragmentation in Cavite resulted to slight variability in anuran species diversity and has no pronounced effects on the species richness which appeared to be affected by the presence of streams or riparian areas. H and richness were highest in riparian forests during both dry and wet seasons. Anuran abundance decreased in smaller forest fragments. Twenty-one (21) microhabitats were identified and 47.9% of anurans occurred only in forest floor litter. A total of 174 tree species was identified. The fragments had high HÌ values and even tree species distributions. All fragments, except Palay-Palay, were classified as semi-deciduous forests (SDFs) while all were classified as early second growth (ESG) forests except Evercrest. There were significant variations between fragments and between habitats for all 21 habitat variables tested. PCA was able to extract 3 factors which together accounted for 68.38% of the variability. The niche widths and niche positions of the 17 anuran species along the axes confirmed preference for either forest habitats or riparian areas. Many of the 'specialists' endemic species had narrow niche widths and as a consequence are more prone to habitat disturbances or species extirpation. Occupancy estimates were affected by the species' mode of life and restricted distribution which contributes to species rarity. Best-fit occupancy models for different anuran species included 4 to 17 habitat covariates, making them far more sensitive than reptiles and birds. Generally, forest restricted species were more sensitive to the effects of forest fragmentation compared to forest edge species and generalist species. The occupancy of the species is not dictated by fragment size but is more dependent on the survival envelops. The availability of data on anuran speciesmicrohabitat associations, vegetation profile, and existing anthropogenic threats are thus crucial in the management and conservation of these forest fragments including the diverse array of fauna and flora associated with these areas.